Principles and applications of organic light emitting diodes (OLEDs) - Kalyani, N. Thejo; Swart, Hendrik; Dhoble, S. J. (Woodhead Publishing series in electronic and optical materials., 2017)
Principles and Applications of Organic Light Emitting Diodes (OLEDs)explores the ways in which the development of organic semiconductor materials is opening up new applications in electronic and optoelectronic luminescent devices. The book begins by covering the principles of luminescence and the luminescent properties of organic semiconductors. It then covers the development of luminescent materials for OLEDs, discussing the advantages and disadvantages of organic versus inorganic luminescent materials. The fabrication and characterization of OLEDs is also covered in detail, including information on, and comparisons of, vacuum deposition and solution techniques. Finally, applications of OLEDs are explored, including OLEDs in solid-state lighting, colored lighting, displays and potential future applications, such as ultra-thin and flexible technologies. This book is an excellent resource both for experts and newcomers to the field of organic optoelectronics and OLEDs. It is ideal for scientists working on optical devices, lighting, display and imaging technologies, and for all those engaged in research in photonics, luminescence and optical materials. Provides a one-stop guide to OLED technology for the benefit of newcomers to the field of organic optoelectronicsComprehensively covers the luminescent properties of organic semiconductors and their development into OLED materialsOffers practical information on OLED fabrication and their applications in solid-state lighting and displays, making this essential reading for optoelectronics engineers and materials scientists.